PWE-094 The severity of steatosis does not influence liver stiffness measurements in patients with non-alcoholic fatty liver disease. (17th June 2017) - Forlano, R; Mullish, BH; Angkathunyakul, N; Goldin, E; Yee, M; Serviddio, G; Giannakeas, N; Tzallas, AT; Tsipouras, MG; Rui, F; Khan, S; Taylor-Robinson, S; et al.
Abstract : Introduction: Non-invasive characterisation of hepatic steatosis and fibrosis based on Fibroscan elastographyand controlled attenuation paratmeter (CAP) is used widely for diagnosis and follow up in NAFLD. The aim of this study was to assess the correlation between the degree of steatosis as determined by CAP and the degree of fibrosis by liver stiffness measurements unisg the fat and collagen quantitation as gold standard. Method: 80 consecutive patients with biopsy confirmed NAFLD and transient elastography with CAP score.Biopsies were digitalized at 2x magnification and then analysed by our automated software.Fat and fibrosis quantitation wereexpressed as percentages of the relative areas of fat and collagen respectively and of tissue. Results: Correlation between CAP score and fat% was statistically significant (p=0.002, Rho=0.45). Regression analysis revealed an R2=0.206 (figure 1a). The AUROC foridentifying fat >5% was 0.82(p=0.001, 95%CI=0.71–0.92) with the best cutoff at 250 dB/m (95% sens, 60% specificity).Correlation between liver stiffness and fibrosis quantitation (%) was statistically significant (p<0.001, Rho=0.802) with anR2 of 0.679 (figure 1b).When our cohort was split to those with fat%≤10% and>10% in the liver biopsies there was no difference between liverstiffness and fibrosis quantitation in Pearson's correlation: Rho=0.883 and Rho=0.843 respectively (figure 2). Conclusion: Liver stiffness is a reliable noninvasive tool for estimating the severity of fibrosis in NAFLD. The presenceof severe steatosis evaluated by fat quantitation in liver biopsies did not influence liver stiffness measurements. Disclosure of Interest: None Declared